The miraculous from the material : understanding the wonders of nature - Lightman, Alan P., 1948- (Pantheon Books, 2024)
"A gorgeously illustrated exploration of the science behind the universe's most stunning natural phenomena--from atoms and unicellular life to rainbows, snowflakes, spider webs, the rings of Saturn, galaxies, and more Nature is capable of extraordinary phenomena. Standing in awe of those phenomena, we experience a feeling of connection to others, to wildlife, or to the cosmos. For acclaimed physicist and novelist Alan Lightman, just as remarkable is that all of what we see around us--from soap bubbles and scarlet ibses to shooting stars--are made out of the same material stuff, and obey the same rules and laws. This is what Lightman calls "spiritual materialism," the belief that we can embrace spiritual experiences without letting go of our scientific worldview. Pairing 36 beautiful, full-color photos evoking some of nature's most awe-inspiring phenomena with accessible, lyrical essays, The Miraculous from the Material explores the fascinating science underlying the natural world. Why do rainbows make an arc? Why does a particular waterfall at Yosimite National Park sometimes glow like it's on fire? How does a hummingbird fly? The world has so many things to marvel at--and the science is just as fascinating. Lightman journeys from the world of atoms and molecules to the animal kingdom, from places like Ha Long Bay, Vietnam and the Grand Canyon out to the solar system and beyond, illuminating the unbelievable majesty of the cosmos the remarkable science behind how it got to be the way it is. The Miraculous from the Material is a stunning, soaring ode to the beauty and wonder all around us"--